Efektifitas Sukrosa Oral Terhadap Respon Nyeri Akut Pada Neonatus Yang Dilakukan Tindakan Pemasangan Infus - Ratna Sari Dewi; Wasisto - Utomo; Jumaini - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Pain is an unpleasant sensory and emotional experience and associated with actual or potential tissue damage. Acute pain response of neonates can be evaluated from the response behavior, physiological, and  facial expressions by using a pain scale: premature infant pain profile (PIPP). The purpose of the study is to determine the effectiveness of 24% oral sucrose solution in acute pain response during IV insertion procedure. This study used a pre- experimental design with one-group pretest-posttest design with a sample of 10 mature infants ( ≥ 37 weeks gestation ). Administration of 1 ml of sterile water 2 minutes before IV insertion is done when the pretest and administration of 1 ml of 24% oral sucrose solution  2 minutes before the infusion is done when the posttest. The study was conducted at  Ibu Sina Hospital Pekanbaru. Sampling using probability sampling technic with the purposive sampling type. Analysis of the data using univariate and bivariate analysis (test wilcoxon). The results showed 24 % oral sucrose solution is effective  against acute pain response of neonates during IV insertion with p value of 0,020 (p < 0,05). Recommendation of this study is: administration of 24 % oral sucrose solution needs to be applied in providing nursing care to infants as a non-pharmacological therapy to reduce acute pain response during IV insertion. Keywords : acute pain response , IV  insertion, sucrose.